Mechano-electric coupling in P(VDF–TrFE)/spin crossover composites. Issue 18 (6th April 2020) - Piedrahita-Bello, Mario; Martin, Baptiste; Salmon, Lionel; Molnár, Gábor; Demont, Philippe; Bousseksou, Azzedine
Abstract : Spin crossover particles dispersed in a piezo/ferroelectric poly(vinylidene fluoride- co -trifluoro-ethylene), P(VDF–TrFE), matrix give rise to inspiring mechano-electric phenomena, with possible applications for energy harvesting and sensing. Abstract : Spin crossover particles dispersed in a piezo/ferroelectric poly(vinylidene fluoride- co -trifluoro-ethylene), P(VDF–TrFE), matrix give rise to inspiring mechano-electric phenomena, with possible applications for energy harvesting and sensing. Particles of different chemical compositions, morphologies and concentrations were loaded into copolymers with different TrFE molar contents to investigate the effect of these parameters on the mechano-electric coupling between the polymer and the spin crossover material. The samples were characterized by elemental analysis, powder X-ray diffraction, Raman spectroscopy, optical reflectivity, differential scanning calorimetry, and electron microscopy and were studied also for their piezo/pyroelectric properties. We show that it is possible to tune simultaneously the spin transition temperature of the particles and the Curie temperature of the matrix in such a way that the piezoelectric effect from the spin transition and the pyroelectric response of the polymer can be concomitantly observed. This result provides prospects for the development of smart, multifunctional electroactive polymer composites and for increasing their thermal–electrical harvester output.